Contemporary Nepali Arts: Some Shocking Trends - Sharma, Yam Prasad (Journal of Fine Arts Campus, 2021)
In contemporary Nepali arts, there are some trends that shock any sensible viewer or any informed person in the area. Some artists repeat the same subject matter, figure and technique throughout their life or from the beginning of their profession till now. The presentation of the same thing all the time creates monotony and nausea in the viewers. The question arises: how can an artist do the same thing all the time? Some artists see the works of famous western artists in art history books, art magazines and the world wide web, and they copy their subject matters and techniques thinking that they can create works and be famous. Some artists randomly splash and pour colors on the canvas and say that the mess and confusion in the canvas is abstract art. They opine that nobody can understand abstract art. They are fooling the viewers. Some artists call themselves modern Nepali artists, for they have practiced modern techniques of western arts. Some artists print the photograph on the canvas, make the photograph rough using paints and call it their paintings thinking that the viewers will be fooled. Some artists do realistic paintings with sweats and tireless efforts to earn their livelihood but when it comes to the exhibition of artworks, they make abstract paintings in few minutes. We can find such naïve and shocking trends in some senior artists as well, and young artists following their footprints. As a result, a substantial portion of Nepali art has already entered the whirlpool presenting its non-existent situation which demands immediate rescue from real artists and intellectuals. The scenario of art can be an analogy of the social and political situation of Nepal. We talk about great revolutions, changes and achievements but the situation of people is getting worse and civilization has been degenerated.